A psicose ordinária e seus índices: uma investigação à luz da clínica borromeana - Marconi Martins da Costa Guedes (2014)
This thesis has as a research subject the ordinary psychosis and its types of manifestations in the current psychoanalytic clinic. We carefully discuss the notion of ordinary psychosis and their theoretical and clinical unfolding, questioning above all what are its leads and conceptual foundations, seeking to perform its reading in Jacques Lacan´s formulations of the Borromean clinic. The current clinic has revealed a growing number of psychotic patients who do not show up in the usual form of triggered psychosis, since they do not manifest the expected elementary phenomena, such as the mental automatism, hallucinations, delusions, language disorders and the absolute certainties, but a new order of phenomenon. The elaborations of Jacques-Alain Miller about the ordinary psychoses have enabled us to perform a reading of these psychoses and its modes of presentation, whose clinical presentations are marked by manifestations of certain social disconnection, body and subjective, showing the presence of what Miller characterized as a neotriggerings, neoconvertions and neotransfers in contemporary clinical. Considering the perspective opened by the Borromean clinic, the notion of ordinary psychosis, although not a new clinical structure nor a category of Lacan, can be taken as a construction supported by his last teaching. Within these assumptions, a psychosis may not necessarily have such a clear triggering, this fact expands the clinical perspective and asks for more rigor when doing a differential diagnosis, especially in face of the subtleties of its leads and ways of presentation. In this context, the ordinary psychosis requires a bifid diagnosis to be identified: in one hand it is necessary to define the signs of the failing of the borromean node and in the other hand, it is also necessary to distinguish by wich means this defect that has been compensated by the subject. In this sense, our hypothesis is that in ordinary psychosis each subject must invent its own sinthomatic solution to compensate its structural lack, thus relying on an additional device that must be built as a way to together sustain the registers of the Real, the Symbolic and the Imaginary.